Effect of CYP3A4 Inhibitors and Inducers on Pharmacokinetics and Pharmacodynamics of Saxagliptin and Active Metabolite M2 in Humans Using Physiological-Based Pharmacokinetic Combined DPP-4 Occupancy - Li, Gang; Yi, Bowen; Liu, Jingtong; Jiang, Xiaoquan; Pan, Fulu; Yang, Wenning; Liu, Haibo; Liu, Yang; Wang, Guopeng (Frontiers in Pharmacology, 2021)
We aimed to develop a physiologically based pharmacokinetic and dipepidyl peptidase 4 (DPP-4) occupancy model (PBPK-DO) characterized by two simultaneous simulations to predict pharmacokinetic (PK) and pharmacodynamic (PD) changes of saxagliptin and metabolite M2 in human when co-administration with CYP3A4 inhibitors or inducer. Ketoconazole, delavirdine and rifampicin were selected as CYP3A4 competitive inhibitor, time-dependent inhibitor (TDI) and inducer. Here, we have successfully simulated PK profiles and DPP-4 occupancy profiles of saxagliptin in human using PBPK-DO model. Additionally, under the circumstance of actually measured values, predicted results were good line with observations, and all fold-errors were below 2. The prediction results demonstrated that oral dose of saxagliptin should be reduced to 2.5 mg when co-administrated with ketoconazole. The predictions also showed that although PK profiles of saxagliptin occurred significant changes with delavirdine (AUC:1.5-fold increase) or rifampicin (AUC: decrease to 0.19-fold) than without inhibitor or inducer, occupancies of DPP-4 by saxagliptin were nearly unchanged, that is, administration dose of saxagliptin needn’t to adjust when co-administration with delavirdine or rifampicin.